The Holy One of Israel studies in the book of Isaiah - Oswalt, John N., 1940- (Cambridge : James Clarke, 2014)
In the course of 30 years dedicated study, John N. Oswalt has written a number of articles in journals and chapters in books on the book of Isaiah as a whole, or some aspect of it. These materials have here been collected in a single volume and arranged in something of a descending order, that is from more general treatments of the book as a whole and how he sees the parts contributing to the whole, to studies of themes, such as holiness, righteousness, the nations, and finally to treatments of specific segments.
9. God's Determination to Save His People10. The Significance of the Calmah Prophecy in the Context of Isaiah 7-12; 11. Isaiah 24-27: Songs in the Night; 12. Isaiah 52:13-53:12: Servant of All; 13. Isaiah 60-62: The Glory of the Lord; Back cover.
CIP data; item not viewed.
Master record variable field(s) change: 050
Keywords: Bible. -- Commentaries; Bible; Bible. Isaiah -- Criticism, interpretation, etc; Bible. Isaiah -- Criticism, interpretation, etc. -- History; Bible. Isaiah -- Theology; Bible. Isaiah; RELIGION -- Biblical Studies -- Prophets; Electronic books; Commentaries